Guest

(secA-cosecA)(1+tanA+cotA)=tanA secA-cotA cosecA

(secA-cosecA)(1+tanA+cotA)=tanA secA-cotA cosecA

Grade:

1 Answers

Askiitians_Expert Yagyadutt
askIITians Faculty 74 Points
11 years ago

Hello Krishna !

 

It is very simple ...Just multiply each terms in LHS you will get the result ..

 

(secA - cosecA)(1+tanA+cotA)

 

= secA + tanA.secA + cotA.secA - cosecA - cosecA.tanA - cosecA.cotA

 

= secA + sinA.sec^2A + cosecA - cosecA - secA - cosec^2A.cosA

 

= sinA/cos^2A - cosA/sin^2A

 

= (sinA/cosA)secA - (cosA/sinA)cosecA

= tanA.secA - cotA.cosecA ( RHS )

 

Hence proved ...

 

Regrads

 

Yagya

Askiitians_expert

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free